NEW DATA ON THE LOWER CAMBRIAN BIOSTRATIGRAPHY OF THE EASTERN SAYAN - Dyatlova I.N.; Sycheva R.F. (My University, 1999)
Geological mapping of the Eastern Sayan in the late 1980s-early 1990s proved the occurrences of stable assemblages of archaeocyathids and trilobites correlatable with those from horizons of the Altai-Sayan foldbelt (except for the Ust'-Kundat Horizon). Archaeocyathids and trilobites provide reliable correlations of the Kiya, Kameshki, Sanashtykgol, and Obruchev horizons both within the Eastern Sayan area and between the neighboring areas of the Altai-Sayan foldbelt. The small-shelled fauna associated with archaeocyathids in the Lower Cambrian sequences allow us to accurately date basal Cambrian beds barren of archaeocyathids near the Vendian boundary. Of interest are the occurrences of small-shelled forms typical of the Tommotian Stage in the Natal'evka, Kiya, Kameshki, and Sanashtykgol horizons.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская